Real-world clinical impact of first-line immune checkpoint inhibitor-based therapy in advanced esophageal squamous cell carcinoma - M. Tamba; K. Chin; H. Osumi; M. Ogura; S. Fukuoka; S. Udagawa; K. Shimozaki; K. Yoshino; T. Wakatsuki; E. Shinozaki; K. Yamaguchi; A. Ooki (ESMO Gastrointestinal Oncology)
Background: Chemotherapy (chemo) combined with an immune checkpoint inhibitor (ICI) or dual ICI therapy with nivolumab and ipilimumab (nivo + ipi) is the standard first-line treatment for patients with advanced esophageal squamous cell carcinoma (ESCC). In this study, we evaluated real-world clinical outcomes for first-line ICI-based therapy and explored its prognostic factors. Patients and methods: This single-center retrospective study included patients with ESCC who received ICI-based therapy between January 2021 and July 2024. Results: In total, 92 patients received either ICI + chemo (n = 60) or nivo + ipi (n = 32). The median progression-free survival and overall survival (OS) were 5.0 and 16.0 months for ICI + chemo and 3.5 and 16.9 months for nivo + ipi, respectively. Of the 70 patients with measurable lesions, early tumor shrinkage (ETS) was achieved in 37% for ICI + chemo and 33% for nivo + ipi. ETS was significantly associated with a lower performance status and neutrophil-to-lymphocyte ratios, but not with the treatment regimen or programmed death-ligand 1 (PD-L1) status. Patients who achieved ETS showed significant tumor reduction and a durable response. ETS was an independent predictor of favorable OS (hazard ratio 0.34, 95% confidence interval 0.11-0.88, P = 0.04), whereas neither the treatment regimen nor the PD-L1 status influenced OS. Immune-related adverse events of grade ≥3 occurred in 12% of patients. Conclusions: First-line immunotherapy is effective and safe for the treatment of patients with ESCC. Rapid and deep tumor shrinkage may serve as an early predictive biomarker for longer survival.